The Roles Of Sphingosine-1-Phosphate (S1p) On Arthritis: Review Article - HUTAMI, ISLAMY RAHMA (Odonto : Dental Journal, 2024)
Arthritis is a pathological condition that results in degeneration of the joints. RA and OA are the most common types of arthritis. RA is a chronic joint inflammation caused by the immune system's self-attack on tissues. By contrast, OA is chronic joint inflammation caused by cartilage breakdown. Both illnesses cause joint discomfort, stiffness, and edema. One genetic factor in arthritis is sphingosine-1-phosphate (S1P). S1P regulates bone homeostasis and growth using 5 receptors: 1, 2, 3, 4, and 5. Thus, this literature review intends to investigate the impact of S1P on arthritis. Methods: The eligibility criteria comprised cross-sectional studies that were published in English until January 2024 and exclusively addressed the role of S1P in arthritis. Results and discussion: From 396 publications, 17 relevant articles were located, and 6 were chosen for the review. The S1P/S1P2 signaling pathway releases osteoclasts to degrade cartilage in osteoarthritis. S1P also promotes bone growth by differentiating osteoblasts and forming blood vessels in the bone marrow. The miR-25 rs41274221 polymorphism may reduce osteoporosis risk. IL-6 is also produced by osteoblasts with S1P. Osteoarthritis is associated with elevated blood S1P and MMP-3 levels. Cyclic strain and inflammation increase Sphk1 upregulation and S1P release, suggesting a role in osteoarthritis. In conclusion, the expression of S1P by osteoclasts, osteoblasts, chondrocytes, and tenocytes is believed to play a crucial role in regulating cell migration and the production of cytokines or chemokines throughout the process of bone formation. Focusing on the S1P pathway may help treat bone and joint diseases.